Salmonella Agona Outbreak from Contaminated Aniseed, Germany - Koch, Judith (Centers for Disease Control and Prevention, 2005)
A nationwide outbreak of Salmonella Agona caused by aniseed-containing herbal tea occurred from October 2002 through July 2003 among infants in Germany. Consumers should adhere strictly to brewing instructions, although in exceptional cases this precaution may not be protective, particularly when preparing tea for vulnerable age groups.